Investigation of the prerequisites for the optimization of specific plasma protein binding as a strategy for the reduction of first-pass hepatic metabolism. (3rd November 2014) - Svennebring, Andreas Mats
Abstract: 1. It is hypothesized that the deliberate structural tailoring of compounds designed for drug use to increase the specific plasma protein binding can be used to reduce first-pass hepatic metabolism. To test the feasibility of this hypothesis, a dataset of drugs with plasma protein binding of 90% or above divided into three classes including 50 acids, 44 bases and 69 neutrals was analyzed. 2. Among the drugs with ≥99% plasma protein binding, the fraction of the total dose existing in free form in vivo (free dose fraction) decreased in the following order: acids (0.55%) > neutrals (0.16%) > bases (0.08%). The order was different for the fraction of the total dose that existed in plasma protein bound form (plasma protein bound dose fraction): acids (58%) > neutrals (17%) = bases (18%). 3. The free fraction was poorly correlated with the partition coefficient (Log P ). The lower aqueous solubility associated with high plasma protein binding was explained by differences in Log P and not by the plasma protein binding per se . The logarithm of the extrarenal clearance was correlated with Log P . For acids and bases, extrarenal clearance was also correlated with fu . For neutrals, plasma protein binding had no protective effect.